Menstrual poverty among adolescents from a state school in Rio Verde – Goiás (Research, Society and Development, 2023)
Objectives: To investigate the prevalence and effects of menstrual poverty among adolescents at a state school in the city of Rio Verde – Goiás. Methods: This is a cross-sectional, observational and descriptive study based on the analysis of touches answered by elementary and high school students at a state education center in the city of Rio Verde. The validated “About the Menstrual Practice Needs Scale (MPNS-36)” was used as a model. Results: In the school environment, a significantly smaller proportion of girls always had access to menstrual materials (22.6%) and a clean place to change them (34.8%) compared to home – 90.8% and 88, 3%, respectively. 35.3% of the participants reported having missed classes because they were menstruating, which correlated, above all, with the concern that the menstrual flow would leak (78.6%). In addition, 61% of adolescents are always and often concerned that someone sees the disposal of their pads and 48.6% always receive information about the menstrual cycle. Conclusions: The unavailability of menstrual hygiene materials in the school environment, taboos and stigmatization about the menstrual cycle were found to be determining factors in the prevalence of menstrual poverty in Rio Verde – GO. Therefore, it is necessary to massively encourage public health programs that guarantee access to menstruation.